Beyond patent expiry: development of a model for pricing generic drugs in South Africa - Keele, Mothobi Godfrey (My University, 2017)
Background: Generic drugs provide a safe, effective and affordable alternative to medicines whose patent protection has expired. The affordability of generics improves access to medicines and thus improves health outcomes. The generic pharmaceutical industry is complex; profitability depends on the number of other generics on the market. Objective: To develop a model that explains structural relationships in the off-patent market between the price of a generic drug and the characteristics of a drug, formulation market and regulatory processes in the South African pharmaceutical industry. Sources of Data: Innovators’ drugs and their generic equivalents were selected from all the molecules whose patents expired between 1999 and 2012. Data were obtained from IMS Health (Total Private Market Report) and National Department of Health (Database of Medicine Prices) for the patents’ expiration dates, prices, sales, launch dates of generics, therapeutic groups, schedules, and dosage forms of drugs in the sample. Principal Findings: Generic entry into the local pharmaceutical industry is low, slow and selective. The developed model for this study identified seven market variables that were found to have an influence on the prices of generic drugs in South Africa. The determinants of generic entry are the market size of the on-patent innovator product, and the complexity of manufacture of a dosage form. The introduction of the transparent pricing system has had a significant impact in reducing the average unit prices of generics in South Africa. However, there appears to be policy incoherencies between the public health and industrial policies of the South African government as it pertains to pharmaceuticals. The erosion of the manufacturing capacity in South Africa could potentially be attributed to the pharmaceutical pricing policy. The overreliance on pharmaceutical imports for satisfying local consumption poses a risk to the security of supply of medicines in a country that has a high burden of diseases. Conclusion: The introduction of legislative reforms related to the pricing of medicines in South Africa has largely yielded positive results in making medicines to be more accessible. Policy-making requires monitoring and evaluation programmes and inclusivity across all the stake-holders.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2017.
Keywords: Drugs--South Africa; Generic drugs--South Africa